ARTIFICIAL INTELLIGENCE IN ESP INSTRUCTION: OPPORTUNITIES AND CHALLENGES (World Bulletin of Education and Learning, 2026)
This study explores the role of artificial intelligence (AI) in English for Specific Purposes (ESP) instruction, focusing on both its opportunities and challenges. In recent years, AI technologies have increasingly been integrated into language education, offering innovative tools such as intelligent tutoring systems, chatbots, and adaptive learning platforms. These technologies enable personalized learning, real-time feedback, and enhanced interaction, which are particularly beneficial in ESP contexts where learners require domain-specific language skills. The research analyzes how AI supports the development of professional communication competencies and improves learning outcomes. At the same time, the study highlights challenges related to technological accessibility, data privacy, and the potential reduction of human interaction in the learning process. The findings suggest that while AI significantly enhances ESP instruction, its effective implementation requires a balanced pedagogical approach.
Keywords: artificial intelligence, ESP, language teaching, adaptive learning, intelligent tutoring systems, chatbots, professional communication, digital education, educational technology, challenges and opportunities.